Adaptive Leadership And Employee Work Productivity; A Literature Review - Ringgo Ivan Saputra; Havis Aravik (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
The changes in the increasingly dynamic work environment necessitate organizations to have leaders who can swiftly adapt to various challenges. Adaptive leadership has emerged as a relevant leadership approach in addressing the complexities and uncertainties faced by modern organizations. This article aims to examine the concept of adaptive leadership and its relationship with employee productivity based on various scientific literature. The method employed is a literature review of books, national and international journals, and relevant scientific publications. The findings indicate that adaptive leadership positively influences employee productivity by enhancing motivation, work engagement, innovation capabilities, and flexibility in task completion. Therefore, the implementation of adaptive leadership can serve as a crucial strategy for organizations to improve performance and competitiveness